Tourists Generation Z: Features of Perception of Marketing Incentives and Advertising - Bakina, Tetiana; Бакіна, Тетяна Володимирівна; Бакина, Татьяна Владимировна; Tkachuk, U. (My University, 2020)
Focusing on the preferences of Generation Z in tourism is one of the latest trends in developed countries. Generation Z is a term used for people born since 1995. Often the term "Generation Z "is used as a synonym for the term" digital person" because they appeared in the era of mobile phones, computers and the Internet. By the end of 2020, Generation Z will become the largest population group in the world, so it makes sense for businesses that want to maintain their position in the market and develop to pay attention to their preferences and consumer habits.
Keywords: tourism; Generation Z; digital person